Confraternities and the Church in Late Medieval Florence - Henderson, John (Studies in church history, 1986)
The confraternities of late-medieval Europe have been seen as associations which were in some ways almost independent of the Church, and drew their special dynamism from the fact that the parish was supposedly in decline and had ceased to provide an adequate religious service to the lay community. However true this may have been north of the Alps, the problem when this proposition is applied to southern Europe, and particularly Italy, is that very little is known about the late-medieval parish to ascertain whether confraternities were really syphoning off the adherence of the local inhabitants. So often our impressions about the state of the Italian church derive from the sporadic visitations of local bishops or the ribald stories of a Boccaccio or Franco Sacchetti, later repeated and taken almost at face value by such influential writers as Burkhardt. But we may also be in danger of seeing late-medieval religion filtered through sixteenth-century eyes and taking for granted the correctness of the criticisms of the Council of Trent or for that matter following Luther’s gripes that confraternities had become no more than beer-drinking clubs.